2019
DOI: 10.1007/s00382-019-05030-6
|View full text |Cite
|
Sign up to set email alerts
|

Tropical climate variability in the Community Earth System Model: Data Assimilation Research Testbed

Abstract: A new prototype coupled ocean-atmosphere Ensemble Kalman Filter reanalysis product, the Community Earth System Model using the Data Assimilation Research Testbed (CESM-DART), is studied by comparing its tropical climate variability to other reanalysis products, available observations, and a free-running version of the model. The results reveal that CESM-DART produces fields that are comparable in overall performance with those of four other uncoupled and coupled reanalyses. The clearest signature of difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In a related study using CESM-DART (Eliashiv et al, 2018), the data assimilation in CESM significantly improved the performance of MJO events, which suggested that the flux coupling at the ocean-atmosphere interface may be important in organizing the convective activity inherent in MJO. Focusing on MJO events, which have well-known mechanisms involved, may give us added insight into the processes leading to the error growth in CESM-DART.…”
Section: Intraseasonal Explorationmentioning
confidence: 96%
See 1 more Smart Citation
“…In a related study using CESM-DART (Eliashiv et al, 2018), the data assimilation in CESM significantly improved the performance of MJO events, which suggested that the flux coupling at the ocean-atmosphere interface may be important in organizing the convective activity inherent in MJO. Focusing on MJO events, which have well-known mechanisms involved, may give us added insight into the processes leading to the error growth in CESM-DART.…”
Section: Intraseasonal Explorationmentioning
confidence: 96%
“…For instance, since the study was executed in observations space, there was no assessment of the reliability of the surface fluxes because they were not included in the data assimilation procedure (cf. Eliashiv et al, 2018 who found enhanced MJO activity may be due to the surface flux coupling in CESM-DART). Additionally, evaluations using ensemble-based reanalysis products with more properly specified observational uncertainty and the high-density observations that are available in more recent decades may also provide clearer perspectives on how to pinpoint the processes in the model that need the most improvement in their parameterization.…”
Section: 1029/2019ms001678mentioning
confidence: 98%